Mechanism for hydrolysis of double six‐membered ring tetraborate anion. Issue 5 (23rd November 2019) - Zhou, Hongxia; Zhu, Fayan; Liu, Hongyan; Zhang, Wenqian; Zhou, Yongquan; Fang, Chunhui
Abstract: [B4 O5 (OH)4 2− ] is a representative borate anion with a double six‐membered ring structure, but there is limited knowledge about the hydrolysis mechanisms of [B4 O5 (OH)4 2− ]. Density functional theory‐based calculations show that the tetraborate ion undergoes three‐step hydrolysis to form [B(OH)4 − ] and an ring intermediate, [B3 O2 (OH)6 − ]. Other new structures, such as linear trimer, branched tetraborate, analogous linear tetraborate, are observed, but they are not stable in neutral systems and change to ring structures. [B3 O2 (OH)6 − ] hydrolyzes to [B(OH)4 − ] and [B(OH)3 ] in the last two steps. The structure of borate anion and the coordination environment of the bridge oxygen atom control the hydrolysis process. [B4 O5 (OH)4 2− ] always participates in the hydrolysis reaction, even with a decrease in concentration. [B3 O3 (OH)4 − ], [B(OH)4 − ], and [B(OH)3 ] have different roles in "water‐poor" and "water‐rich" zones. Concentration and pH of solution are the key factors that affect the distribution of borate ions. Abstract : Tetraborate ion undergoes three‐step hydrolysis to form [B(OH)4 − ] and an ring intermediate [B3 O2 (OH)6 − ]. Other structures, such as linear trimer, branched tetraborate, analogous linear tetraborate, are not stable in neutral systems and change to ring structures. [B3 O2 (OH)6 − ] hydrolyzes to one [B(OH)4 − ] and two [B(OH)3 ] isomers in the last two steps. Both the structure of borate anion and coordination environment of the bridge oxygen atom control the hydrolysis process.